Birth and Developing of Mongolian Geoscientist journal - Takahashi, Yuhei; Ichinnorov, Niiden; Jargalan, Sereenen; Batkhishig, Bayaraa (Mongolian Geoscientist, 2021)
Since the publication of the first issue of Mongolian Geoscientist, in October 1996, 25 years have passed and the journal has successfully evolved over a quarter of a century into a periodical publication well-known also outside the borders of Mongolia. Background and episodes of early publications were reviewed by Y.Takahashi, N.Ichinnorov, and S.Jargalan, who were members of the JICA-IGMR project. The present status of Mongolian Geoscientist is that of an internationally peer-reviewed, open-access journal, published by the School of Geology and Mining Engineering, Mongolian University of Science and Technology, with support from the Geological Society of Mongolia; managed by Editor-in-Chief B.Batkhishig, Consultant Editorial Board member O.Gerel, and Associate Editors B.Munkhtsengel, B.Altanzul, and Kh.Tseedulam.